2008
DOI: 10.1016/j.neuron.2008.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Prestin-Based Outer Hair Cell Motility Is Necessary for Mammalian Cochlear Amplification

Abstract: It is a central tenet of cochlear neurobiology that mammalian ears rely on a local, mechanical amplification process for their high sensitivity and sharp frequency selectivity. While it is generally agreed that outer hair cells provide the amplification, two mechanisms have been proposed: stereociliary motility and somatic motility. The latter is driven by the motor protein prestin. Electrophysiological phenotyping of a prestin knockout mouse intimated that somatic motility is the amplifier. However, outer hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
345
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 349 publications
(364 citation statements)
references
References 52 publications
16
345
1
2
Order By: Relevance
“…If SFOAEs can be used to assay frequency selectivity, they would provide a more tractable approach for characterizing stimulus coding independent of cochlear location. Preliminary data are provided for wildtype and prestin V499G/Y501H KI mice (referred to here simply as 499) expressing a mutant prestin and showing reduced sensitivity [8]. The SFOAE data from 499 KI mice show loss of sensitivity and no frequency selectivity consistent with previous reports using [2,7], this approach allows us to study the BM-OHC-TM system in young mutant mice and their controls.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…If SFOAEs can be used to assay frequency selectivity, they would provide a more tractable approach for characterizing stimulus coding independent of cochlear location. Preliminary data are provided for wildtype and prestin V499G/Y501H KI mice (referred to here simply as 499) expressing a mutant prestin and showing reduced sensitivity [8]. The SFOAE data from 499 KI mice show loss of sensitivity and no frequency selectivity consistent with previous reports using [2,7], this approach allows us to study the BM-OHC-TM system in young mutant mice and their controls.…”
Section: Introductionsupporting
confidence: 74%
“…Recordings were made in wildtype and prestin 499 KI mice [8] bred on site. All animals were anesthetized with ketamine/xylazine and rectal temperature was maintained at ∼38°C using a heating blanket.…”
Section: Methodsmentioning
confidence: 99%
“…Post hoc t tests also showed that Otoa KOs with high-frequency SOAEs (average SOAE frequency 18.4 kHz) were statistically different (p G 0.01) from KOs with only low-frequency SOAEs at f2 = 17.8 kHz. For comparison, we appended our results from mice lacking prestin to show highlevel OAEs measured in a cochlea where the outer hair cells lack somatic electromotility and, hence, amplification (Dallos et al 2008). The data were obtained from Prestin KOs that produce DPOAEs since emissions in mice lacking prestin are known to be highly variable such that only those with the best sensitivity generate DPOAEs and then only at high stimulus levels (Liberman et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…One group of efferents, the medial olivocochlear (MOC) efferents, innervates outer hair cells (OHCs) and controls the gain of mechanical amplification within the cochlea (Cooper and Guinan 2006). Cochlear amplification is produced by OHC receptor currents causing audiofrequency changes in the length of OHCs that amplify cochlear mechanical responses to sound (Dallos et al 2008). MOC fibers synapse on OHCs and produce an OHC hyperpolarization that reduces the effect of Electronic supplementary material The online version of this article (doi:10.1007/s10162-009-0163-1) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%